Phase equilibrium diagram of the Hf-Fe-Sn system at 1070 K - Romaka, L.; Romaka, V.V.; Stadnyk, Yu.; Pashkevych, V. (Physics and Chemistry of Solid State, 2021)
Experimental studies of the phase equilibrium diagram of the Hf-Fe-Sn ternary system at 1070 K were performed by X-ray powder diffractometry, scanning electron microscopy and electron probe microanalysis techniques in the whole concentration range. At annealing temperature four ternary compounds are realized: Hf6FeSn2 (K2UF6 structure type, space group P-62m), Hf1.8Fe5Sn3.8 (Hf1.82Fe5Sn3.82 structure type, space group Cmmm), Hf3Fe4Sn4 (Zr3Fe4Sn4 structure type, space group Pnma), and Hf9Fe3.7Sn10.3 (Hf9Fe4Sn10 structure type, space group Cmc21). An existence of the Hf1-xFe2+x-ySny solid solution formed by substitution of the iron atoms by tin in the Hf1-xFe2+x (MgZn2-type) binary compound up to 19 at. % Sn was found. Solubility of Fe in the Hf5Sn3 binary (Mn5Si3-type) extends up to 10 at. % (a=0.8363(2)-0.8324(4), c=0.5726(1)-0.5686(4) nm).